Open Pyelolithotomy in a Pelvic Ectopic Kidney: Case Report and Current Literature Review - Hadisuryo, Suharjendro; Hadi, Ewaldo; Danurdoro, Aria (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Advances in urology have significantly reduced the indications for open surgery to treat staghorn kidney stones. Nevertheless, according to our experience, open surgery is still the preferred treatment for rare cases of the ectopic pelvic kidney. CASE PRESENTATION: A 49-year-old man complained about pain in the lower umbilical region for five months. The pain drastically changed into a sharp pain two months before. The vital sign is normal; on physical examination, the palpation of the suprapubic area elicits pain when pressed, no mass is detected. The abdominal computed tomography without contrast showed a right ectopic kidney located anteriorly of the fifth lumbar to the second sacrum. There was also mild hydronephrosis (grade I) and staghorn stones measuring 4 cm x 2.3 cm. The stone was surgically treated with open pyelolithotomy through a midline infra umbilical incision. The patient was discharged five days postoperatively without distinct complications. CONCLUSION: Open surgery can represent a valid alternative in the treatment of kidney stones of very selected cases, including anomalous kidneys, in a setting where resources are limited.